Larrikins, bush tales and other great Australian stories - Seal, Graham (Allen & Unwin, 2014)
Yarns, legends, myths, jokes and anecdotes are our national lifeblood. The home-grown and borrowed tales, told and re-told over generations, offer an insight into the larger national story of which every Australian has a part. Was Breaker Morant the Gatton murderer? What happened to Sniffling Jimmy and Black Mary? We revisit some of the most colourful characters in Australia's past, and the stories that have grown around them. We go looking for the real illywhacker and find out what happened after the execution of our most famous outlaw, Ned Kelly. It takes a certain character to make a living in the Australian bush. In the most difficult situations, laughter often comes to the rescue. Here are pioneers and battlers, convicts and settler's children, and a land that tests them with fire, flood and drought, all in stories resonant with Australia's distinctive wry humour. Dip into Larrikins, Bush Tales and Other Great Australian Stories for a taste of Australia's rich history and traditions.